Leitura : uma prática para a inovação nas organizações - Uveda, Valdecir Pereira (My University, 2014)
The writing divided the history of mankind and has revolutionized the ways of production and transmission of knowledge. A initial, simple and creative action of incision on clay tablets has created both a writer and a reader, and unleashed the revolutionary process of preservation of individual and collective memory. In this context, this study aimed to investigate how reading, such as individual and collective construction of knowledge, can be significant in view the organizational environment for innovation. This is an exploratory study conducted by multi case study, which investigates the presence of reading practice in the strategy, policies or practices of the organizational stratus: strategic, intermediate and operational; from three organizations chosen by the forum of innovation of 2009, produced by FGV-EAESP. Based on a review of literature that focuses on reading and innovation; more specifically on the concepts of innovation, reading, knowledge management, procurement practices, knowledge and organizational learning, were realized interviews with representatives from the stratus of three companies in order to explore the elements of reading and its contribution to innovation. The special features of the method is to analyze the data through intra case and inter case research strategy; to enhance the policies, practices and the actor who most contribute to the development of innovation in these organizations. The results indicate the presence of relevant reading practices, implemented and induced in the organizational strategy, but also used in the everyday practice of each company. [resumo fornecido pelo autor]
A escrita dividiu a história da humanidade e revolucionou as formas de produção e transmissão de conhecimentos. Um ato inicialmente simples e criativo de incisão em tabuletas de argila produziu escritor e leitor simultaneamente e desencadeou o processo revolucionário de preservação da memória individual e coletiva. Neste contexto, esta pesquisa teve por objetivo estudar de que forma a leitura, como construção individual e coletiva de conhecimentos, pode ser significativa no ambiente organizacional em vista da inovação. Trata-se de estudo exploratório realizado por meio de pesquisa multicaso, que investiga a presença da prática de leitura na estratégia, nas políticas ou práticas, dos estratus organizacionais: estratégico, intermediário e operacional, em três organizações eleitas pelo fórum de inovação FGV-EAESP em 2009 como inovadoras. Após revisar a literatura enfocando a referência leitura e inovação nos temas – inovação, leitura, gestão do conhecimento, práticas de aquisição do conhecimento e aprendizagem organizacional – entrevistaram-se representantes dos estratus das três empresas, a fim de explorar os elementos da leitura e sua contribuição para a inovação. As particularidades foram analisadas em suas dimensões intracaso e na intersecção dos dados intercaso sinalizando políticas, práticas e atores que mais contribuem para o desenvolvimento da inovação nestas organizações. Os resultados apontam a presença de práticas de leituras relevantes, implementadas e utilizadas na estratégia organizacional, mas também utilizadas na prática cotidiana de cada empresa. [resumo fornecido pelo autor]
Keywords: Aprendizagem educacional; Leitura - Administração; Gestão do conhecimento -- Administração; Aprendizagem individual; Aprendizagem organizacional; Individual learning; Collective learning